Exploring Talent Management, Learning Organization, and Innovation in Medical Representative Performance - Muhammad Irfan Nasution; Muhammad Taufik Lesmana; Jufrizen; Silvia Ramadhani Faradhilla (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyse the effect of talent management practices, including talent recruitment practice, training and development practice, and compensation practices, on Medical Representative performance, with the mediation of organisational learning and innovative behaviour. Based on data collected from companies in the pharmaceutical industry sector in Medan City, Indonesia, with a sample size of 260 and sampling techniques using accidental sampling, the data analysis technique uses Structural Equation Modelling (SEM - PLS) with SEM PLS 4.0 software. The study’s results indicate that talent management practices (talent recruitment, training and development, and compensation practices) significantly positively affect sales performance. Only talent recruitment does not directly affect Medical Representative performance but hurts learning. In addition, learning organisations are proven to mediate the relationship between talent management practices and Medical Representatives. At the same time, innovative behaviour also plays a role in mediating the effect of talent management practices on Medical Representative performance. These findings provide insight for practitioners in designing more effective sales force management policies in improving sales performance and highlight the importance of learning organisations and innovative behaviour as the main supporting factors.